Design and evaluation of an educational platform for implementing and testing bilateral control algorithms - Cogollor, J. M.; Galiana, I.; Barrio, J.; Ferre, M.; Aracil, R. (Proceedings of the 2012 IEEE Global Engineering Education Conference (EDUCON), 2012)
This paper describes the design and evaluation of a new platform created in order to improve the learning experience of bilateral control algorithms in teleoperation. This experimental platform, developed at Universidad Politécnica de Madrid, is used by the students of the Master on Automation and Robotics in the practices of the subject called "Telerobotics and Teleoperation". The main objective is to easily implement different control architectures in the developed platform and evaluate them under different conditions to better understand the main advantages and drawbacks of each control scheme. So, the student's tasks are focused on adjusting the control parameters of the predefined controllers and designing new ones to analyze the changes in the behavior of the whole system. A description of the subject, main topics and the platform constructed are detailed in the paper. Furthermore, the methodology followed in the practices and the bilateral control algorithms are presented. Finally, the results obtained in the experiments with students are also shown.